Application of Effective Day Degrees in the Assessment of Stable Isotope Patterns in Developing Seahorses under Different Temperatures - Sonia Valladares; Miquel Planas (Animals, 2020)
Relations between nutrient assimilation and growth rate in fishes may vary with abiotic factors such as temperature. The effects of feeding status, ontogeny and temperature regimes (15, 18 and 21 °C) on stable isotope (δ13C and δ15N) patterns were assessed in juveniles of the seahorse Hippocampus guttulatus. The use of effective day degrees (D°eff), day degrees (D°) and chronological time (age) were compared as development progress indices. Newborn seahorses were maintained at three temperature levels both deprived of food (5 days) or fed (30 days) on copepods or/and Artemia. Isotopic signatures in fed seahorses clearly differed from those in unfed juveniles. Temperature had a significant effect on δ13C values in fed juveniles throughout the experimental period. δ15N values also varied significantly with age, but not with temperature level. Faster growth and food assimilation in seahorses held at 18 and 21 °C were supported by faster variations in isotopic values. Our findings demonstrate that effective day degrees should be preferred over chronological time as index of developmental progress in temperature fluctuating scenarios or for comparative studios.